ENERGY SAVING TECHNOLOGIES IN HEAT TREATMENT - Y. Tahetsi; S. S. Tkachenko; V. V. Karabeynikov (Литьë и металлургия)
The short characteristic of the Czech company «TACHTECH S. R. O.» is given. The list of production and the services provided by the company TACHTECH are given.